Association between Temporomandibular Joint dysfunction and Stress in Undergraduate BDS Students of Rawalpindi/Islamabad: Temporomandibular Joint Dysfunction and Stress - Khawar, Saadullah; Bari, Nauman; Rao, Ali Hamza; Malik, Ammar Abdullah; Nasir, Shahzad; Kayani, Ayesha (Pakistan Journal of Health Sciences, 2025)
Temporomandibular Joint Dysfunction (TMJD) is a condition linked with psychological factors like stress. Dental students experience high academic stress which makes them an ideal candidate to investigate the relationship between TMJD and stress. Objective: To investigate the association between TMJD and stress in undergraduate BDS students in Rawalpindi and Islamabad. Methods: A cross-sectional study was conducted among 346 BDS students using convenience sampling. Participants completed structured questionnaires, including Fonseca's Anamnestic Index for TMJD and the Perceived Stress Scale. Data analysis was performed using SPSS version 21.0, employing chi-square tests for categorical data and correlation analysis for continuous variables. he study was conducted in two dental institutes namely Margalla Institute of Health Sciences and Foundation University College of Dentistry and Hospital. Results: Out of 346 participants, 264 (76.30%) were females and 82 (23.70%) were males, with a mean age of approximately 20.7 years. The result of the chi-square test for the association between gender and TMJD was a statistically significant relationship (p = 0.00033), with females showing higher rates of mild and moderate TMJD compared to males, whereas the chi-square test for the association between the year of study and TMJD also indicated a significant relationship (p = 0.023). Conclusions: This study found a significant association between stress and Temporomandibular Joint Dysfunction (TMJD) among undergraduate BDS students.